Synthesis of Pd-Ag/C electro-catalysts and their activities for ethanol oxidation in alkaline media - Law, Hiu Mung. (2009)
Bimetallic Palladium-Silver electro-catalysts supported on carbon black (Pd-Ag/C) were synthesized and tested for its performance for ethanol oxidation in alkaline media. The synthesis method using NaBH4 reduction method allows formation of Palladium (Pd) and Silver (Ag) nano-particles. X-Ray Diffraction (XRD) and Transmission Electron Spectroscopy (TEM) were performed to determine the surface and morphology of the electro-catalysts.